IMPROVEMENT OF THE MECHANISM OF DEVELOPMENT OF INNOVATION COMPETENCE OF FUTURE TEACHERS IN THE PROCESS OF INDEPENDENT EDUCATION (The Role of Exact Sciences in the Era of Modern Development, 2023)
This article describes the issues of developing special competencies of future teachers of technological education based on an integrative approach in the educational process, as well as the processes of improving the mechanism of developing innovative competence of future teachers in the process of independent education.